Development and Determination of the Parameters of a Capacitive Seed Sowing Sensor for Row Crops - Anatoliy I. Zavrazhnov; Yakov P. Lobachevskiy; Nikita Yu. Pustovarov (Сельскохозяйственные машины и технологии)
Abstract. The development of a universal control system requires designing unified seed sowing sensors that allow controlling the sowing of seeds of different crops. (Research purpose) To provide theoretical grounds for the determination of parameters and installation location of a capacitive seeding sensor. (Materials and methods) In the course of the study, the authors have made theoretical calculations of the seed travel trajectories in mechanical and pneumatic sowing machines using the Mathcad and Microsoft Excel software systems, at various sowing machine frequencies: 11.5; 17.5 and 26.0 revolutions per minute as well as the calculation of the electrical parameters of the designed seeding sensor. Laboratory studies of the trajectory have been performed at the same rotational speeds of the sowing unit disc using high-speed seeding surveys on an experimental installation with subsequent processing of the obtained video materials. The optimum installation angle of the sensor has been experimentally studied from 0 to 67.5 degrees with a pace of 22.5 degrees to minimize the travel time of seeds through the sensitive area of the sensor, and as a result, to increase the sensor resolution using the developed software. (Results and discussion) Geometric and electrical parameters of the designed sowing sensor have been obtained, and its optimum location has been determined. (Conclusions) In the course of laboratory studies, data similar to the calculation results have been obtained; the relative value of the convergence coefficient between experimentally obtained and theoretical indicators does not exceed 0,55, provided these values are obtained at a distance less than the radius of seeds. The authors have experimentally determined the minimum distance between the sensor plates, which amounts to 20 millimetre, and calculated the electrical parameters of the sensor. They have also stated that the height of the sensitive zone should be at least 5 millimeters for reliable metering of individual seeds under these conditions. The obtained data allowed designing an experimental seeding sensor to determine the optimum angle and the sensor installation site. It has been concluded, that in order to minimize the travel time of seeds in the sensitive area of the sensor, the latter should be installed perpendicularly to the flight trajectory of the seeds.